Determination of Differentiating Markers in Coicis Semen From Multi-Sources Based on Structural Similarity Classification Coupled With UPCC-Xevo G2-XS QTOF - Zhu, Ruyi; Xu, Xiaofen; Shan, Qiyuan; Wang, Kuilong; Cao, Gang; Wu, Xin (Frontiers in Pharmacology, 2020)
Coicis Semen, a medicinal food, is derived from the dried and mature seeds of Coix lacryma-jobi L. var. mayuen (Roman.) Stapf, a member of the Gramineae family. Lipids are its main constituents. Previous literatures had reported that Coicis Semen contains 20 triglycerides and 12 diglycerides. However, we identified 35 triglycerides, 16 diglycerides, 4 monoglycerides, and 2 sterols under the preoptimized conditions of UPCC-Xevo G2-XS QTOF combined with a personalized TCM database. Furthermore, we successfully determined glycerol trioleate content to evaluate quality differences. Finally, we identified the fatty acid compositions of 7 of 9 differential markers via Progenesis QI by using principal component analysis, orthogonal projection to latent structures–discriminant analysis, and LipidMaps database. In addition, we applied software-based classification, a method that was previously developed by our team, to verify and predict structurally similar compounds. Our findings confirmed that UPCC-Xevo G2-XS QTOF combined with software-based group classification could be used as an efficient method for exploring the potential lipid markers of seed medicine.